2021
DOI: 10.2174/1871527319666200910153431
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of a Novel Proposal for Antioxidant Treatment Against Brain Damage Occurring in Ischemic Stroke Patients

Abstract: : The underlying mechanism of cerebral injury occurring in patients with acute ischemic stroke involves a key pathophysiological role of oxidative stress. Thus, reactive oxygen species are related to the development of brain edema, calcium overload, mitochondrial dysfunction, excitotoxicity, iron release and inflammation. Nevertheless, although experimental studies have tested the use of antioxidants as an adjuvant therapy in this setting, clinical data and randomized trials are still lacking. Current approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…It is suggested that oxidative stress may be one of the mechanisms inducing ferroptosis in cerebral stroke. During IR, neuronal cells in the penumbra may be subjected to oxidative stress caused by pro-oxidants ROS and reactive nitrogen species (RNS) ( Orellana-Urzúa et al, 2021 ). ROS comprise free radicals such as ·OH and superoxide (O 2 − ) as well as some nonradical molecules such as H 2 O 2 , whereas commonly observed RNS are nitric oxide (NO·) and peroxynitrite (ONOO − ) ( Prasad et al, 2019 ).…”
Section: Mechanisms Of Ferroptosis In the Pathogenesis Of Ischemic Strokementioning
confidence: 99%
“…It is suggested that oxidative stress may be one of the mechanisms inducing ferroptosis in cerebral stroke. During IR, neuronal cells in the penumbra may be subjected to oxidative stress caused by pro-oxidants ROS and reactive nitrogen species (RNS) ( Orellana-Urzúa et al, 2021 ). ROS comprise free radicals such as ·OH and superoxide (O 2 − ) as well as some nonradical molecules such as H 2 O 2 , whereas commonly observed RNS are nitric oxide (NO·) and peroxynitrite (ONOO − ) ( Prasad et al, 2019 ).…”
Section: Mechanisms Of Ferroptosis In the Pathogenesis Of Ischemic Strokementioning
confidence: 99%
“…The opposite process would be an increase in the generation of free radicals, which can happen through intracellular mitochondrial dysfunction, or through an extracellular source such as inflammation, as discussed above. The time-course of oxidative stress is initially mitochondria-mediated, for example, due to oxygen and glucose deprivation and following mitochondrial depolarization, and is then xanthine oxidase-mediated, NOS-induced and later NADPH oxidase-mediated [ 20 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In stroke, the results of ROS imbalance are considerable and include apoptosis, blood-brain barrier (BBB) disruption, inflammation, edema formation, autophagy and other pathophysiological events [ 20 ]. ROS and RNS are generated mainly by microglia and astrocytes [ 28 ].…”
Section: Oxidative Stress In the Brainmentioning
confidence: 99%
“…The basic cause of neurological impairment caused by IS is a brain injury of nerve cell death or apoptosis, acute phase for brain energy metabolism disorder caused by glucose and oxygen supply and oxygen free radical formation, nerve cells Ca2+ overload, the formation of excitatory amino acids and noninfectious inflammatory reaction, resulting in a large number of nerve cell necrosis and apoptosis, causes corresponding neurological defects, including hemiplegia, motor, sensory, language dysfunction, etc. [4,5]. What's more, cerebral embolism induced by nerve damage or vascular blockage caused by hypoxia is the leading cause of IS, and oxidative stress, inflammatory, and blood-brain barrier failure play a huge role in this process [6].…”
Section: Introductionmentioning
confidence: 99%